"I Can't Think of a More Unlikely Rock Star than Me": Representations of "Averageness" in the Myth of Rock. Issue 3 (1st September 2016) - Walus, Scott M.; Click, Melissa A.
Abstract : Media texts introduce individuals to "the myth of rock" and define rock's members and possibilities. Although any individual can theoretically tap into the power of rock, these texts construct "ordinariness" and "averageness" as requirements for access to the supposed meritocracy of American rock. Through analysis of eight episodes of Behind the Music and five Hollywood films about rock, we demonstrate that, despite the myth of rock's assertions of egalitarianism, it privileges and excludes along the lines of identity categories. Specifically, the myth privileges masculinity, heterosexuality, and whiteness, and relegates anyone who does not fit into "other" status.